THE EFFECT OF USING DUOLINGO APPLICATION THROUGH STUDENTS VOCABULARY TO THE TENTH-GRADE AT SMKN 1 SOJOL UTARA - Rahmatul Ummu Arifin; Nahdawati Nahdawati; Siti Aisyah (Scolae: Journal of Pedagogy, 2025)
This research aims to find out the Effect of using the Duolingo application can improve the students’ vocabulary mastery or not. This research used quantitative research. The research methodology of this research is quasi – experimental design. The population of this research was class X SMKN 1 Sojol Utara with consisting of 76 students. The sample of this research was class X TKJ A consisting of 30 students as the experimental group and class X NKPI consisting of 16 students as the control group. The experimental group was taught using the Duolingo application media while the control group used conventional teaching. Data analysis in this research used the SPSS program. The results of data analysis show that t – table (2.01) is lower than t – count (7.13). The results of the research concluded that H0 was rejected and H1 was accepted. Based on the results of data analysis, it can be concluded that the use of the Duolingo application provides an Effect for students in vocabulary learning in tenth-grade at SMKN 1 Sojol Utara.